Pengolahan Film Radiografi Secara Otomatis Menggunakan Automatic X-Ray Film Processor Model Jp-33 - Andre Afani, Zoucella; Rupiasih, Ni Nyoman (BULETIN FISIKA, 2017)
A research on the process of forming an image on a radiographic film and processing techniques automatically has been done. The study was conducted using an X-ray plane Toshiba E 7239, Fil AGFA Healtcare HV Septestraat 27B2640 Mortsel and an automatic film processing "Automatic X-Ray Film Processor Model JP-33". The experimental results showed that the principle of automatic film processing is the same as the principle of film processing manually, except in automatic film processing there is no rinsing stage. Automatic film processing can save time and costs; also it can reduce the possibility of errors due to human factors.